(untitled) - Trimmer, Joseph F. (Boston, 1988)
Short Edition: Writing With A Purpose has always been distinguished by its emphasis on the role of purpose in the writing process, its comprehensive coverage of the materials and problems basic to the introductory writing course, and its effective use of examples and exercises to illustrate how writers make decisions that produce successful writing.
Keywords: English language,English language,Anh ngữ thực hành,Anh ngữ thực hành; Rhetoric,Grammar,Tu từ học,Ngữ pháp